2021
DOI: 10.1016/j.rbmo.2020.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Is there an optimal number of oocytes retrieved at which live birth rates or cumulative live birth rates per aspiration are maximized after ART? A systematic review

Abstract: Is there an optimal number of oocytes retrieved where live birth rates or cumulative live birth rates per aspiration are maximised after ART? A systematic review,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…It is noteworthy that 12-15 oocytes optimised cumulative LBR, as with conventional IVF (Law, et al, 2021, Magnusson, et al, 2018, the only difference being that there was no incidence of severe OHSS in our study population. In conventional IVF however, high cumulative LBR is accompanied by a rising OHSS rate (Drakopoulos, et al, 2016), even when an agonist trigger is used (Connell, et al, 2019).…”
mentioning
confidence: 74%
“…It is noteworthy that 12-15 oocytes optimised cumulative LBR, as with conventional IVF (Law, et al, 2021, Magnusson, et al, 2018, the only difference being that there was no incidence of severe OHSS in our study population. In conventional IVF however, high cumulative LBR is accompanied by a rising OHSS rate (Drakopoulos, et al, 2016), even when an agonist trigger is used (Connell, et al, 2019).…”
mentioning
confidence: 74%
“…This study did not report a plateau in cumulative live birth rate and a further increase of 5% was detected beyond 27 oocytes. A recent systematic review of 16 studies (comprising five studies evaluating live birth rate from fresh cycles, five studies evaluating cumulative live birth rate from stimulated cycles and six studies evaluating both) suggested that 12–18 oocytes was the optimal number of oocytes associated with maximal fresh live birth rate, whereas cumulative live birth rate continued to increase with the number of oocytes retrieved ( 45 ).…”
Section: Results Of the Consensus And Actionable Recommendations (Including Supportive Evidence)mentioning
confidence: 99%
“…Patients' characteristics are summarized in Table 1. The age, basal follicleforming hormone (bFSH), dose of Gn, duration of Gn, and the proportion of patients with type B PCOS were significantly higher in the low-oocyte group (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11) than in the middleoocyte group (12)(13)(14)(15)(16)(17) and high-oocyte group (18-62) (p < 0.05). The body mass index (BMI), and total testosterone were significantly higher in the low-oocyte group than in the highoocyte group (p < 0.05).…”
Section: Patients' Characteristicsmentioning
confidence: 99%
“…In the implementation of IVF, the increased number of oocytes retrieved improved pregnancy rates in women by increasing the number of available embryos for transfer (1). The number of oocytes retrieved is an important factor affecting the cumulative live birth rate, and the cumulative live birth rate (CLBR) increases with the increase in the number of oocytes retrieved (2)(3)(4). However, increasing the number of oocytes retrieved not only increases the incidence of ovarian hyperstimulation syndrome (OHSS) and other complications but also increases the possibility of whole embryo freezing, which prolongs the treatment cycle of patients.…”
Section: Introductionmentioning
confidence: 99%